Factors affecting activation and utilization of carbon dioxide in cyclic carbonates synthesis over Cu and Mn peraza macrocyclic complexes - Srivastava, R.; Bennur, T. H.; Srinivas, D. (Journal of Molecular Catalysis A - Chemical, 2005)
The catalytic activities of several Cu and Mn aza complexes for cyclic carbonate synthesis from CO2 and epoxides are reported. The various factors affecting activation of CO2 by metal complexes and its utilization in cyclic carbonate synthesis have been investigated. Fr-IR, UV-vis and EPR spectroscopic investigations reveal that CO2 coordinates to Cu in eta(1)-C mode of coordination. Nature of the ligand and substitution influence the lability of metal-CO2 bonding. The differences in the catalytic activities are correlated with the mode and strength of CO2 binding. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: benign synthesis; Carbon dioxide; catalysis by Cu and Mn complexes; CO2 activation; CO2 fixation; CO2 utilization; cyclic carbonates; polycarbonates; spectroscopy

Reverse microemulsion mediated sol-gel synthesis of lithium silicate nanoparticles under ambient conditions: Scope for CO2 sequestration - Khomane, Ramdas B.; Sharma, B. K.; Saha, S.; Kulkarni, B. D. (Chemical Engineering Science, 2006)
We report on the synthesis of nanocrystalline lithium silicate by coupling of sol-gel method in reverse microemulsion. The sample calcined at 800 degrees C gives pure phase lithium metasilicate nanocrystallites. X-ray diffraction and transmission electron microscopy confirmed the formation of nanocrystalline lithium silicate particles with a narrow size distribution. The nanoparticle prepared in the microemulsion shows enhanced CO2 sorption capacity and shorter retention times at higher temperature (similar to 131 ml/g at STP at 610 degrees C which are better than the best known results. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; Carbon dioxide; Microemulsion; particle; separations; sol-gel; surfactant

Gas permeation in amine functionalized silicon rubber membranes - Achalpurkar, Manoj P.; Kharul, Ulhas K.; Lohokare, Harshada R.; Karadkar, Prasad B. (Separation and Purification Technology, 2007)
Silicon rubber (SR) based thin film composite (TFC) membranes find increasing applicability in various industrial separations owing to its excellent thermal and chemical stability. The functionalization of SR would provide enhanced separation characteristics for certain separation applications. The present research focuses on gas permeation properties of dense and thin film composite membranes based on amine substituted silicon rubber (ASR) and unsubstituted silicon rubber (SR). The dense membrane sorption analysis indicated that presence of amine functionality in ASR increased pressure dependant CO2 sorption capacity. Owing to this, an elevation Of CO2 permeability by 15% and CO2 based selectivities by 22-34% in comparison to that of unsubstituted SR was observed. The TFC membranes with SR and ASR as the selective layer on the top of different ultrafiltration (UF) supports with varying properties based on polyacrylonitrile and polysulfone were prepared. The effects of crucial parameters that affected TFC membrane performance, viz., coating solution concentration, UF support membrane porosity and nature of materials were investigated. The preparation of ASR based TFC membranes was demonstrated with a simple crosslinking agent-glutaraldehyde while analyzing effects of crosslinking time on their permeation properties. Polyacrylonitrile (PAN) was found to be better support layer material for ASR based TFC formation than polysulfone (PSF). Thin defect free coating layer can be obtained by appropriate combination of coating solution concentration and support UF membrane porosity. The analysis of effective skin layer thickness of TFC membranes indicated that careful optimization of these parameters is necessary to achieve defect free TFC membranes possessing a good combination of permeance and selectivity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; Gas permeation; silicon rubber; thin film composite membrane

Reactions in supercritical carbon dioxide - Mayadevi, S. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Use of conventional organic solvents often leads to the formation of hazardous waste, the disposal of which is a matter of environmental concern. Carbon dioxide is considered to be a green reaction medium and a good replacement for conventional organic solvents as it is benign and leads to elimination/reduction of hazardous wastes. Use of CO2 at near/above critical conditions has several additional advantages as the reactions can be pressure-tuned to eliminate transport resistance, increase solvent power and heat capacity. Hence, there has been considerable interest in the use of supercritical carbon dioxide as either a replacement of conventional organic solvent or as a co-solvent in reactions. Herein, recent developmenst in this area during the last decade is reviewed, specifically in gas-liquid (organic hydrogenation, hydroformylation and oxidation) and liquid-liquid (carbon-carbon coupling, alkylation, acetylation, esterification) reactions.
Keywords: Alkylation; Carbon dioxide; Hydroformylation; Hydrogenation; Oxidation; Supercritical carbon dioxide

Sodium-doped lithium zirconate nano squares: synthesis, characterization and applications for CO2 sequestration - Khokhani, Mrinal; Khomane, Ramdas B.; Kulkarni, Bhaskar D. (Journal of Sol-Gel Science and Technology, 2012)
Nano squares of sodium-doped lithium zirconate have been synthesized by a simple citrate based sol-gel method at room temperature in the presence of cetyl trimethylammonium bromide (CTAB) as a surfactant. The structural and morphological properties were investigated by X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) respectively. XRD analysis of sample calcined at 900 A degrees C for 4 h shows the formation of monoclinic lithium zirconate phase. The TEM shows the interesting morphology of formation of nano squares of sodium doped lithium zirconate sample. The carbon dioxide sorption capacity was carried out by TGA analysis at different high temperatures. It is observed that the sample shows similar to 20 wt% carbon dioxide sorption at higher temperature (650 A degrees C) within 20 min which are better than the known reports.
Keywords: Carbon dioxide; CTAB; Lithium zirconate; Sodium doped lithium zirconate; sol-gel; TEM; XRD

Effects of method of preparation on catalytic activity of Co-Zn double-metal cyanide catalysts for copolymerization of CO2 and epoxide - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2014)
Co-Zn double-metal cyanide (DMC) complexes are well-known catalysts for ring-opening polymerization of epoxides and co-polymerization of CO2 and epoxides. This work provides an insight on structure-activity relationship of DMC for poly(cyclohexene carbonate) synthesis. Seven samples of DMC were prepared by different methods and mode of reagent addition. Highly active catalyst could be synthesized even without using a co-complexing agent. CO2 adsorption studies revealed that higher the guest-host interaction higher would be the catalytic activity. High density and strength of Lewis acid sites, moderate crystallinity, low crystal symmetry (rhombohedral/monoclinic), Cl- ions and coordinated tert.-butanol (complexing agent) control the catalytic activity for polycarbonates. Chloride in the structure avoided induction period by increasing acidity of the catalyst and thereby, improving the guest-host interactions. Polycarbonates with CO2 incorporation as high as 86 mol%, average molecular weight of 20900 and polydispersity index of 1.8 were prepared at complete conversion of cyclohexene oxide. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; CO2 utilization; Copolymerization of CO2 and cyclohexene oxide; Double-metal cyanide; Polycarbonate; Structure-activity relationship

Hydrogenation of polar bonds catalysed by ruthenium-pincer complexes - Balaraman, Ekambaram; Milstein, David (Ruthenium in Catalysis, 2014)
Catalytic hydrogenation of polar bonds using molecular hydrogen is an important, atom-economical synthetic reaction. Classical reduction methods of polar bond often require reactive metal-hydride reagents in stoichiometric amount and produce copious waste. Hydrogenation of carbonyl compounds in particular provides `green' approaches to synthetically important building blocks, such as alcohols and amines. We have designed and synthesized several ruthenium-based pincer catalysts for unprecedented hydrogenation reactions including: (1) amides to alcohols and amines, (2) biomass-derived di-esters to 1,2-diols and (3) CO2 and CO derivatives to methanol. These atom-economical reactions operate under neutral, homogeneous conditions, at mild temperatures, mild hydrogen pressures, and can operate in absence of solvent with no generation of waste. The postulated mechanisms involve metal-ligand cooperation (MLC) by aromatization-dearomatization of the heteroaromatic pincer core.
Keywords: Amides; Carbon dioxide; Esters; Hydrogen; Hydrogenation; Metal-ligand cooperation; Pincer complexes; ruthenium

One-pot synthesis of cyclic carbonates from aldehydes, sulfur ylide, and CO2 - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Synlett, 2014)
Treatment of aldehydes with sulfur ylide (CH2=SOMe2 or CH2=SMe2), in the presence of CO2 (1 atm) bubbled sequentially under mild conditions, produces cyclic carbonates in preparative yields. Sodium iodide formed in situ promotes the reaction between epoxide as intermediate and CO2 at ambient conditions, thus constituting a powerful metal-free synthesis of organic cyclic carbonates directly from aldehydes.
Keywords: Carbon dioxide; cyclic carbonates; cyclization; epoxides; Insertion

Effect of different fixed bed media on the performance of sodium dodecyl sulfate for hydrate based CO2 capture - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Kumar, Pushpendra; Balomajumder, Chandrajit (Materials & Design, 2016)
Sodium Dodecyl Sulfate (SDS) is used as a kinetic promoter in gas hydrate formation. In this work, the performance of SDS for carbon dioxide gas hydrate formation in two different fixed bed media: silica sand and zeolite (5A and 13X) has been evaluated. The concentration of SDS was fixed at 0.5 wt%. The experiments were carried out in batch mode with the initial pressure fixed at 3.0 MPa, and the temperature kept constant at 274.65 K. The results showed that hydrate of carbon dioxide with fixed bed of silica sand was significantly promoted by the addition of SDS as compared to the other fixed bed medium used in this study: zeolite 13X. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide; Fixed bed media; Hydrate formation; Kinetic promoter; Silica sand; Zeolite 5A and 13X

Rapid synthesis of zwitterionic phosphonium benzoates by a three-component coupling involving phosphines, arynes and CO2 - Bhattacharjee, Subrata; Raju, Anjali; Gaykar, Rahul N.; Gonnade, Rajesh G.; Roy, Tony; Biju, Akkattu T. (Chemistry-An Asian Journal, 2020)
A mild and easy to perform multicomponent coupling involving phosphines, arynes generated from 2-(trimethylsilyl)aryl triflates, and CO(2)allowing the transition-metal-free synthesis of zwitterionic phosphonium benzoates has been developed. The reaction proceeds via the generation of 1 : 1 zwitterionic intermediates from phosphines and arynes followed by the interception with CO(2)to deliver the carboxylates in moderate to good yields instead of the anticipated benzooxaphosphol-3(1H)-ones.
Keywords: arynes; Carbon dioxide; multicomponent coupling; Phosphines; zwitterions

Continuous flow synthesis of hierarchical low silica X zeolite - Adarsh, V. K.; Shrotri, Aadesh R.; Birje, Amit R.; Nandanwar, Sachin U. (Materials Today Communications, 2024)
Zeolites, renowned for their versatile applications in catalysis, adsorption, and ion exchange, have long been synthesized using conventional batch processes. However, the inherent limitations of these methods, such as resource-intensive conditions and inconsistent product quality, underscore the need for a sustainable and efficient approach. In this study, a continuous flow synthesis process was established for the synthesis of industrially important low silica X (LSX) zeolite using a tubular reactor. The synthesis gel was subjected to aging for 5 days at room temperature to facilitate nucleation and crystal growth combined with the fast-heating rate in a tubular reactor at 363 K & 1.1 atm., which in turn produces LSX after 40 min. The synthesized product was confirmed by the XRD, FE-SEM, EDS, XRF, TEM, and N2 adsorption-desorption; the data was compared with the LSX sample synthesized by batch process. The result implies that LSX prepared by continuous flow has a pure phase of LSX with the hierarchical structure, which provides better adsorption capacity of CO2 at 298 K up to 20 bar. Due to continuous flow synthesis, the crystallization time was reduced and faster kinetics which may be helpful for scale-up the process for LSX synthesis.
Keywords: Adsorption; Carbon dioxide; continuous flow; Low silica X; Tubular reactor; zeolites

Performance of Li exchange hierarchical X zeolite for CO2 adsorption and H2 separation - Shrotri, Aadesh R.; Birje, Amit R.; Niphadkar, Prashant S.; V. Bokade, Vijay; Mali, Nilesh A.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2024)
Li exchange hierarchical X zeolite (Li-H-X) was prepared by decationization of X zeolite by NH4Cl solution followed by Li exchange and subsequent calcination. NH4-X and Li-X were prepared to compare the results of LiH-X. XRD, FE-SEM, EDS, N2 adsorption-desorption, and micro-/mesoporous volume were performed. The higher mesoporosity was confirmed in Li-H-X due to the framework dealumination during decationization. Static and dynamic sorption capacity of sorbents was evaluated to identify the performance of sorbent. The CO2 and H2 equilibrium adsorption capacity of Li-H-X was found to be 9.6 mmol g-1 and 0.78 mmol g-1, respectively, at 298 K and 20 bar, which was 25 % (CO2) and 30 % (H2) higher than Li-X. Static experimental data were validated using the Langmuir, Freundlich, and Sips models. The CO2 & H2 dynamic sorption capacity of Li-H-X sorbent for binary gas (CO2/H2, 25/75 %) was 4.145 mmol g-1 and 0.258 mmol g-1 at 303 K and 10 bar. The higher sorption capacity of Li-H-X was obtained due to large micro-/mesoporous volume of sorbent, which may allow to access unoccupied sites at higher pressure. This result reveals that micro-/mesoporous structure of zeolite adsorbs significantly higher CO2 from binary gas stream, which can use to separate pure H2 from gas stream.
Keywords: Adsorption; Carbon dioxide; Hydrogen; Microporous-mesoporous; Separation